Analysis of biological and genetic stability of tick-borne encephalitis strain 205 used in the production of tick-borne encephalitis vaccines EnceVir and EnceVir Neo for children - M. S. Vorobyeva; G. M. Ignatyev; N. A. Netesova; E. V. Otrashevskaya; N. Kh. Stavitskaya; M. S. Shcherbinina; K. A. Sarkisyan; V. A. Shevtsov; A. V. Rukavishnikov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение)
The article presents the results of a long-term study of biological and genetic stability of tick-borne encephalitis strain 205 which is used by the FSUE «SPA «Microgen» to produce tick-borne encephalitis vaccines EnceVir (for adults) and EnceVir Neo for children, both of which are tissue cultured, inactivated, purified, and sorbed. The biological stability of strain 205 was studied at the seed lot stage using passages on outbred white mice: initial production strain 205 and production «stock strain». Lyophilisates of production seed lots were studied at different storage intervals at -20 °С (up to 9 years of storage and more). Biological activity parameters (tick-borne encephalitis virus (TBEV) titre in log LD50/ml) were studied by using different ways of infecting outbred white mice, and strain 205 identification (specificity) was determined by comparing it to a reference strain in a biological neutralization assay (BNA) according to the manufacturer’s specifications for the vaccines concerned. The same materials and a batch of TBEV vaccine produced from the production «stock strain» (lyophilisate of 1986) were analyzed by polymerase chain reaction (PCR) and sequencing for genetic stability during passaging and long-term storage. The results of the study made it possible to demonstrate the biological and genetic stability of strain 205 during production of TBEV vaccines.